Travel guide Kyoto Nara Osaka Kobe (Tokyo, 1972)
This pocket guide book gives you practical information on traveling in Kyoto, Nara, Osaka and Kobe. It will tell you where to stay, what to see, what food to enjoy and what to hunt for sovenirs. With this guide, you will really enjoy your visit in this part of Japan.